Gastroblastoma in a 5-year-old child: a case report and literature review - Feng, Jizhen; Ling, Chunxiang; Xue, Yingjie; Li, Jiamei (Frontiers in Oncology, 2023)
Background Gastroblastoma is an extremely rare stomach tumor with a biphasic cell morphology of epithelioid and spindle cells. Due to the low incidence rate and the lack of specific clinical characteristics, it is easy to misdiagnose. Detailed imaging analysis is also unavailable. At present, we reported a case of gastroblastoma to analyze its clinical and imaging characteristics. In addition, we reviewed the imaging findings, current diagnosis, treatment, and outcome of gastroblastoma. Case presentation A 5-year-old girl was admitted to our hospital with upper abdominal pain and melena. Endoscopic examination showed a protuberant submucosal mass on the greater curvature of the gastric body. Abdominal ultrasonography and an abdominal enhanced computed tomography further confirmed the mass. The patient was pathologically diagnosed with gastroblastoma after radical surgery in February 2021. Conclusion We described a rare case of gastroblastoma and may provide a new perspective on imaging diagnosis, treatment, and outcome of this tumor. Gastroblastoma tends to occur in male patients, typically affects young people, and has low malignant potential and a low rate of recurrence and metastasis. Gastroblastoma usually arises in the gastric muscularis propria with hypoecogenic and submucosal characteristics in ultrasound examination and significant enhancement in computed tomography (CT) scan. Surgical resection and regular follow-up after surgery are the main management of the disease. Clinicians should strengthen the understanding of this rare tumor for early detection and treatment.